Racial/Ethnic Differences in Knowledge, Attitudes, and Beliefs About COVID-19 Among Adults in the United States - Reiter, Paul L.; Katz, Mira L. (Frontiers in Public Health, 2021)
Background: Knowledge, attitudes, and beliefs are cognitive outcomes that serve as key determinants of engaging in health behaviors, likely including vaccination and other mitigation behaviors against coronavirus disease 2019 (COVID-19). Studies have begun examining people's knowledge, attitudes, and beliefs about COVID-19, but little is known about how these cognitive outcomes differ across racial/ethnic groups. Methods: An online survey was conducted with a convenience sample of adults ages 18 and older in the United States (n = 2,006) in May 2020, about 2 months after COVID-19 was declared a pandemic. Multivariable regression models were used to examine differences in knowledge, attitudes, and beliefs about COVID-19 across racial/ethnic groups (non-Latinx white, non-Latinx black, non-Latinx of another race, or Latinx). Results: Knowledge tended to be lower among non-Latinx blacks and Latinx participants compared to non-Latinx whites. For example, fewer non-Latinx blacks responded correctly that COVID-19 is not caused by the same virus that causes influenza (adjusted OR = 0.66, 95% CI: 0.49–0.90), and Latinx participants were less likely to respond correctly that people with COVID-19 do not always show symptoms of being sick (adjusted OR = 0.63, 95% CI: 0.45–0.87). For beliefs and attitudes, non-Latinx blacks (β = −0.09) and non-Latinx participants of another race (β = −0.05) reported lower perceived likelihood of getting COVID-19 in the future compared to non-Latinx whites, while Latinx participants reported greater perceived stigma of COVID-19 (β = 0.08) (all p < 0.05). Conclusions: Several differences in cognitive outcomes about COVID-19 exist across racial/ethnic groups, including gaps in knowledge and varied beliefs and attitudes. Results identify modifiable targets for public health programs promoting vaccination and other mitigation behaviors against COVID-19.